A comparative study of outer membrane proteins of selected Brucella strains - ISLOOR, S; SURYANARAYANA, V V S; RAO, M SATYANARAYANA; RAJASEKHAR, M (The Indian Journal of Animal Sciences, 2014)
Outer membrane proteins (OMPs) of Brucella abortus strains (99,544 and 19), Brucella melitensis 16M and Brucella suis 1330 were isolated by differential centrifugation method, Based on sodium dodecyl sulphate - polyacrylamide gel electrophoresis (SDS-PAGE) profiles, Brucella OMPs were classified into 3 distinct molecular weight (MW) ranges, viz, low MW (14-30 kDa), moderate MW (39-60 kDa) and high MW (68-93 kDa), Polypeptides above 60 kDa were not observed in B, abortus 544. The moderate MW bands were more varied in their migration and relative quantity, Silver staining confirmed the presence of polysaccharide moieties in major bands at position 39,2-47,3 kDa,The subtle differencesÂ observed in SDS-PAGE analysis of Brucella OMPs did not represent rei iable marker for identification of Brucella species.